Spatio-Temporal Assessment of Shoreline Changes and Management of the Transgressive Mud Coast, Nigeria - Popoola, Olusola Olalekan (European Scientific Journal, ESJ, 2022)
This study investigated changes due to erosion and the consequences of rising sea levels on the Transgressive mud coast of Nigeria using multispectral Landsat images and ALOS PALSAR (AW3D30) elevation models with the view of proffering a management strategy for a sustainable coast. Endpoint Rate (EPR) and Linear Regression Rate (LRR) techniques within the Digital Shoreline Analysis System (DSAS) were used to assess the rates of changes along the shoreline between 1986 and 2021. Inundation models were developed in line with sea-level rise scenarios of the Green House Gas emissions (SSP5-8.5) with GIS to assess sea-level rise’s impact on land and structures. Likewise, spatially disaggregated population and economic activity datasets projected to the year 2100 were overlaid on the inundation models to generate exposure indices for the coast. The study revealed that 49.8 km (64.67%) of the shoreline experienced retreat over the entire study period. This rapid rate of shoreline retreat has caused a land loss of 15.1 sq. km to the Atlantic over the last 35 years, which could trigger an additional 1.26 sq. km by the year 2032. Furthermore, the impact of sea-level rise is severe on the transgressive coast triggering submergence of the mud coast by inundation to the extent of 201 sq. km which will increase to 551 sq. km by 2100. Losses in terms of structures, population, and economic activity are recorded. To curtail the ongoing coastal changes, the study recommends the full adoption of the shoreline management plan (SMP) for sustainable shoreline management.